1999
DOI: 10.1023/a:1022153403924
|View full text |Cite
|
Sign up to set email alerts
|

Untitled

Abstract: Ethnic differences in psychopharmacological treatment have received much attention in the last two decades. Most of the research efforts conducted so far in the field of ethnopsychopharmacology have focused on comparative responses to neuroleptics and lithium between white and Asian-American patients, and on comparative responses to tricyclic antidepressants among white, African-American and Hispanic patients. In this article we focus on the response to neuroleptic treatment among white, African-American and H… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2003
2003
2018
2018

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 32 publications
(5 citation statements)
references
References 25 publications
0
5
0
Order By: Relevance
“…Given these health and acculturation relationships, acculturation could potentially affect adherence via, for example, physician/patient communication or health literacy. Ethnic differences in prescriptions for and use of (32, 33), dosing needs (34), response to (35), and tolerability of (36, 37) psychotropics have been previously noted for Latinos. However, to our knowledge, there has not yet been a comprehensive review of the literature examining psychotropic adherence among Latinos living in the United States that includes the frequency of, factors associated with, and influences of language and acculturation on nonadherence.…”
Section: Introductionmentioning
confidence: 94%
“…Given these health and acculturation relationships, acculturation could potentially affect adherence via, for example, physician/patient communication or health literacy. Ethnic differences in prescriptions for and use of (32, 33), dosing needs (34), response to (35), and tolerability of (36, 37) psychotropics have been previously noted for Latinos. However, to our knowledge, there has not yet been a comprehensive review of the literature examining psychotropic adherence among Latinos living in the United States that includes the frequency of, factors associated with, and influences of language and acculturation on nonadherence.…”
Section: Introductionmentioning
confidence: 94%
“…Some studies have demonstrated differences in efficacious doses of antipsychotics, as well as antipsychotic response, among different racial and ethnic groups 13,15,16. However, some other studies have failed to replicate these findings 17,18. Hence, the additional aim of this study was to document differences, if any, in average dose, clinical response, and safety profile of ziprasidone between Chinese and Western populations.…”
Section: Introductionmentioning
confidence: 93%
“…Contrary to general beliefs that African/Black populations require higher doses of psychopharmacological agents than the Caucasian population for the treatment of most psychiatric disorders, recent studies have shown that this is not the case. These studies (Varner et al , 1998, 2000; Ruiz et al , 1999) have shown that African/Black populations require smaller doses of tricyclic antidepressants (desipramine, imipramine and nortriptyline) than the Caucasian population for the treatment of major depression and, similarly, smaller doses of selective serotonin reuptake inhibitors (fluoxetine and sertraline).…”
Section: African/black Populationsmentioning
confidence: 99%